Interactive urban environments - Meyer, Anthony (Kansas State University, 2011)
Interactive technology is rapidly affecting our society, extending opportunities for convenience, communication, function, and pleasure. Defined as electronic or computation-based entities that reciprocate human use or action, interactive technology allows people the opportunity to personalize how something looks, how it feels, what it does, and how it is perceived. Many physical objects, such as a home thermostat system or a motion-activated sculpture, are embedded with computation that allows them to detect certain environmental influences, and respond with a purposeful action. As suggested by Malcolm McCullough, interactive technologies will be implemented into the urban environment, grounding them to a specific place and reflecting the character and context. Interactive technology will be combined with traditional urban design practices to generate an interactive urban environment. The Civic Room in Downtown St. Louis is prime for renewal. Underutilized and monotonous, the park space is seen as a tear in the urban fabric and lacks diverse program opportunities. The Civic Room will be used as a testing ground for an interactive urban environment, utilizing three dimensions of interactive technology, including information exchange, creative expression, and kinetics, as well as the specific elements of an effective urban open space (Whyte, 1980). Then, the existing site and resulting interactive urban environment will be evaluated on its potential to improve certain dimensions of performance (Lynch, 1981), and its impact on the identity and use of the space. Engaging an interactive urban environment in the St. Louis Civic Room will promote an understanding of the effects that interactive technology can begin to have in a larger context. It will activate the space, promote social collaboration, and establish a dynamic atmosphere that reflects more closely the desired intent of all users. In turn, it can propel the opportunity to approach interactive urban environments as an alternative method of urban space design.
Keywords: interactive; technology; St. Louis; urban design; Architecture (0729); Design (0389); Landscape Architecture (0390)